Attention and written expression in school-age, high-functioning children with autism spectrum disorders. (April 2018) - Zajic, Matthew C; McIntyre, Nancy; Swain-Lerro, Lindsay; Novotny, Stephanie; Oswald, Tasha; Mundy, Peter
High-functioning children with autism spectrum disorders often find writing challenging. These writing difficulties may be specific to autism spectrum disorder or to a more general clinical effect of attention disturbance, as these children are often comorbid for attention-deficit/hyperactivity disorder (ADHD) symptomatology (and children with attention-deficit/hyperactivity disorder often also find writing challenging). To examine this issue, this study investigated the role of attention disturbance on writing in 155 school-age children across four diagnostic groups: high-functioning autism spectrum disorder (HFASD) with lower ADHD symptoms (HFASD-L), HFASD with higher ADHD symptoms (HFASD-H), ADHD symptoms but no autism spectrum disorder symptoms, and typical development. Both HFASD subgroups and the ADHD group displayed lower word production writing scores than the typical development group, but the clinical groups did not differ. The HFASD-H and ADHD groups had significantly lower theme development and text organization writing scores than the typical development group, but the HFASD-L and typical development groups were not significantly different. The findings support prior research reporting writing problems in children with autism spectrum disorder but also suggest that children with HFASD-H may be at greater risk for writing difficulties than children with HFASD-L. Better understanding the role of attention in writing development could advance methods for assessment and intervention for children with high-functioning autism spectrum disorder at risk for writing difficulties.